Diurnal variation in gait characteristics and transition speed. (February 2015) - Bessot, Nicolas; Lericollais, Romain; Gauthier, Antoine; Sesboüé, Bruno; Bulla, Jan; Moussay, Sebastien
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the effect of time-of-day on Preferred Transition Speed (PTS) and spatiotemporal organization of walking and running movements. Twelve active male subjects participated in the study (age: 27.2 ± 4.9 years; height: 177.9 ± 5.4 cm; body mass: 75.9 ± 5.86 kg). First, PTS was determined at 08:00 h and 18:00 h. The mean of the two PTS recorded at the two times-of-day tested was used as a reference (PTSm). Then, subjects were asked to walk and run on a treadmill at three imposed speeds (PTSm, PTSm + 0.3 m.s−1, and PTSm − 0.3 m.s−1) at 08:00 h and 18:00 h. Mean stride length, temporal stride, spatial stride variability, and temporal stride variability were used for gait analysis. The PTS observed at 08:00 h (2.10 ± 0.17 m.s−1) tends to be lower (p = 0.077) than that recorded at 18:00 h (2.14 ± 0.19 m.s−1). Stride lengths recorded while walking (p = 0.038) and running (p = 0.041) were shorter at 08:00 h than 18:00 h. No time-of-day effect was observed for stride frequency during walking and running trials. When walking, spatial stride variability (p = 0.020) and temporal stride variability (p = 0.028) were lower at 08:00 h than at 18:00 h. When running, no diurnal variation of spatial stride variability or temporal stride variability was detected.